Accelerating distribution of Muslim inheritance in the light of Irtikāb Akhaf al-Dararayn (Act-on Lesser of The Two Harms) / Saheed Abdullahi Busari - Abdullahi Busari, Saheed (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2023)
Islamic inheritance is one of the ḥudūd in Islamic law that observes strict regulations in the textual evidence. However, the quest for the acceleration of inheritance in recent times is due to fear of greater harm from the violation of the rights of weak heirs since there are reported cases of possible denial of female children, women, underage and baby in the foetus, which requires protection in the estate of the bequeather. This study explores the juristic interpretation of the term "death of the bequeather" as a condition of distributing the estate and the juristic implication of the dire circumstances that may trigger the acceleration before the death of the bequeather in contemporary realities. This study uses the doctrinal approach in the qualitative method to explore the implication of death of the bequeather a primary condition in the distribution of the estate in Islamic inheritance, and the possibility of applying the principle of Akhāfu al-Dararayn to establish the acceleration of distribution of Islamic inheritance. The study found that the quest for the acceleration of the distribution of inheritance is mostly related to the Muslim minority society where Shariah is not recognised and applied in family-related issues triggering the call for a safety net to protect the interest of the weak among the heirs to achieve the higher Shariah objective of protection of family and wealth through the transfer of ownership and benefit. This study suggests the need to assess the implications of applying the principle of Irtikāb akhāfu al-dararayn in the acceleration of wealth distribution.